ARTYKUŁ ORYGINALNY/ORIGINAL PAPEROwn experience in anticytokine treatment - Tłustochowicz, Małgorzata; Malec, Zofia; Bachta, Artur; Jancelewicz, Jacek (Reumatologia/Rheumatology, 2005)
The aim of the study was to assess efficacy and adverse events of TNF-alpha blocking treatment in patients with rheumatoid arthritis refractory to standard disease modifying drugs. Dependent to the access of possible agent 26 patients received infliximab and 10 etanercept. In infliximab group an average time of treatment was 12 months, in etanercept group 8,8 months. In infliksimab group permanent improvement was observed in 22 patients (84%), between them very good in 9 (34%), moderate in 8 (31%) and low in 5 (19%). In 1 patient (4%) improvement was not observed, in 3 (12%) it was transient and followed by exacerbation. Treatment was stopped in 7 patients (28%), due to lack of efficacy in 3 and due to allergic reactions. In etanercept group improvement was observed in 8 patients, between them remission in 3 and very good in 5 (50%). In 2 patients treatment was stopped due to lack of efficacy. In these patients unexpected complications appeared, but were mild and did not require treatment stopping. TNF-alpha blockers proved to be successful and safety treatment worth to be recommended in patients not reacting to other forms of treatment.